Low glycaemic index diets improve glucose tolerance and body weight in women with previous history of gestational diabetes : a six months randomized trial - Shyam, Sangeetha; Arshad, Fatimah; Abdul Ghani, Rohana; Abdul Wahab, Norasyikin; Safli, Nik Shanita; Mohd Yusof, Barakatun Nisak; Chinna, Karuthan; Chinna, Nor Azmi (BioMed Central, 2013)
Background: Gestational Diabetes Mellitus (GDM) increases risks for type 2 diabetes and weight management is recommended to reduce the risk. Conventional dietary recommendations (energy-restricted, low fat) have limited success in women with previous GDM. The effect of lowering Glycaemic Index (GI) in managing glycaemic variables and body weight in women post-GDM is unknown.